Policy actors' perceptions on applying a SDH approach in child health policy in Australia: A cross‐disciplinary approach (public health and political science). Issue 1 (1st April 2021) - Littleton, Clare; Star, Cassandra; Fisher, Matt; Ward, Paul R.
Abstract: Research suggests policy action on the social determinants of health (SDH) is required to reduce child health inequities (HE). However, there has been limited action in this area in Australia. Political will has been identified as a barrier but few public health scholars have conducted research which adopts a political science perspective to explore this issue. This study aims to address this gap in the literature. We conducted 27 semi‐structured interviews with policy actors involved in the development of four Australian child/youth health policies selected as relatively good practice in addressing the SDH and HE. Several political science theories guided the design of the study with the Shiffman and Smith framework predominantly used, and adapted, for analysis. The findings suggest policy development was supported by a cohesive policy network, including credible leaders. Framing of issues varied with early childhood development, health equity, and child rights being clear motivators for change. Policy actors used several tactics to navigate a neoliberal policy environment and promote a SDH agenda including adopting a credible framework; consultation with children/youth; establishing an institute outside of government; engaging medical entrepreneurs; and combining a Public Health and Wellbeing Act with a healthy cities approach. Abstract : This study applies a political science lens to explore policy actors' perceptions on the formulation of four Australian child health policies considered relatively good practice in addressing the SDH. Cohesive policy networks, framing of the issue, and developing tactics to navigate the policy environment were important factors to bring about change.